2003
DOI: 10.1002/app.13302
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing method on the exfoliation process for organically modified clay systems. I. Polyurethanes

Abstract: The influence of different processing methods on the nature of the dispersion achieved in the creation of a polyurethane nanocomposite is presented. The nanocomposites were produced using two different types of organically modified montmorillonite clays and a sample of fine particles of silicon nitride as a reference material. Rheological data were used to assess the nature of the dispersion achieved using the different processing methods. The nature of the dispersion produced was characterized using wide-angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 11 publications
(16 reference statements)
2
48
0
Order By: Relevance
“…There was little difference between the dispersion that contained the LMA and those that did not. In a previous paper, 9 it had been noted that the sonication power level appeared to have an effect on the degree of exfoliation. Using different sonication power levels, mixtures containing 5% (w/w) of Cloisite 30B were investigated (Fig.…”
Section: Laurylmethacrylate As An Aid To Exfoliation and Effects Of Smentioning
confidence: 96%
See 1 more Smart Citation
“…There was little difference between the dispersion that contained the LMA and those that did not. In a previous paper, 9 it had been noted that the sonication power level appeared to have an effect on the degree of exfoliation. Using different sonication power levels, mixtures containing 5% (w/w) of Cloisite 30B were investigated (Fig.…”
Section: Laurylmethacrylate As An Aid To Exfoliation and Effects Of Smentioning
confidence: 96%
“…8 In a previous paper, we reported the use of ultrasound to aid the exfoliation of organically modified montmorillonite (OMMT) in low molar mass poly(propylene glycol). 9 It was shown that in low viscosity media, high shear by itself may not be sufficient to achieve exfoliation. The additional use of ultrasound has been shown to provide an effective route to the dispersion of the OMMT platelets at a nano level.…”
Section: Introductionmentioning
confidence: 98%
“…Ultraturrax high-shear dispersion and PP-g-MA compatibilizer addition along with long alkyl chain for compatibility with PP were reasons for exfoliation of clay layers in the PP matrix. Ultraturrax high-shear dispersion lead to exfoliation of the clay layers, for researchers elsewhere [42,43].…”
Section: Gas Tortuous Theorymentioning
confidence: 99%
“…The difference between various dispersion techniques such as high shear homogenizer and sonifier has also been compared. 7 Sonification can create better dispersion and more stable suspensions but there is evidence that ultrasonic energy can give rise to polymer degradation. 10 The in situ polymerization reaction pathways and kinetics have not been well investigated for PU nanocomposite systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, processing is usually not the focal point of these studies [7][8][9] and normally not investigated systematically. Furthermore, the processing for elastomeric systems tends to be less complex than the more reactive rigid PU systems.…”
Section: Introductionmentioning
confidence: 99%